The Influence of Electronic Word of Mouth Communication on Purchasing Decisions at the Gfshop Online Store - Jaya, Canra Krisna (INJECT (Interdisciplinary Journal of Communication), 2024)
The increasingly tight business world requires business actors to follow technological developments in order to compete with other competitors. The emergence of the marketplace and the high number of marketplace users in Indonesia are opportunities to market and attract consumers’ attention by using communication strategies in their sales. Through the marketplace, someone can share their experiences of products that have been purchased with the hope that potential consumers who read them will be influenced. This study aims to determine the level of electronic word of mouth communication, the level of purchasing decisions of Gfshop followers and the influence of electronic word of mouth communication on purchasing decisions at the Gfshop online store. The theory used in this study is Electronic Word of Mouth, with the valence of opinion dimension, according to Goyette. This study uses a survey method with a simple regression technique. The data collection technique used a Google Forms questionnaire that was given to 100 respondents who follow the Gfshop account, using an accidental sampling technique. Data processing and analysis using SPSS Statistics 22 software. The results of this study indicate that the level of E-WoM communication among Gfshop followers is very high, with a percentage of 66%. The purchasing decisions of Gfshop followers are very high, with a percentage of 52%. There is an influence of E-WoM communication on purchasing decisions at the Gfshop online store, as evidenced by the regression coefficient of 1.243 with a t value of 8.052, which means that the high and low purchasing decisions at the Gfshop online store can be explained through E-WoM communication.